Formulation and Development of Cubed Coffee with Agarwood Leaf Extract Powder - MUHAMMAD, AIMIL; Balkis A. Talip (Enhanced Knowledge in Sciences and Technology, 2024)
Coffee is one of the most popular beverages in our surroundings. A real adventure is hidden behind each hot and flavorful cup of coffee, which can be served in a variety of ways. However, mixed coffee drinks in the form of cubes with the addition of agarwood leaf powder were not available in the market. Therefore, a study was conducted to develop a formulation of coffee cubes with agarwood leaf powder. In this study, consumer acceptability of Aqarwood leaf extract powder was assessed using a 7-point hedonic scale and sensory characteristics were determined using a descriptive test. Untrained and trained panels from UTHM and trained food technology students participated. Skim milk and soymilk formulations were evaluated for appearance, odor, texture, sweetness, bitterness, taste, aftertaste and overall acceptability. Skimmed milk formulation 1 showed the highest acceptance, followed by formulations 3 and 2. Soymilk formulation 3 received the highest acceptance, followed by formulations 2 and 1. Descriptive tests showed significant differences in flavor, bitterness and acidity (p < 0.05). The skim milk formulations showed no differences in overall acceptability, appearance, aroma, texture, bitterness and aftertaste, but differences in taste and sweetness. Soymilk formulations showed differences in overall acceptability, taste, bitterness, sweetness, aftertaste, appearance, aroma and texture.